Drug abuse and anti-drug policy in Japan - Vaughn, Michael (The British journal of criminology, 1995)
This paper traces the abuse of drugs and anti-drug policy in Japan during the pre-war, war, and post-war eras. The analysis is divided into six historical periods that examine the purported antecedents, the historical background, and the various governmental and societal countermeasures adopted to combat the drug problem. Producers, traffickers, and consumers of drugs in Japan are identified and discussed. The paper also addresses drug countermeasures including responses from legislatures, society, criminal justice personnel, and the medical community. The paper argues that Japan's war on drugs' in the 1980s was a direct result of pressure from the United States to adopt harsher sanctions and from a punitive Japanese public that associates drug use with poor self-control. It concludes that Japan should not emulate the punitive policies of the United States because they are inconsistent with historical criminal justice practices in Japan and because little evidence shows they have reduced supply or demand in the United States